HUBUNGAN PEMANFAATAN MEDIA PEMBELAJARAN BERBASIS AUGMENTED REALITY PADA PENINGKATAN MOTIVASI BELAJAR SISWA - Miftah Fadhlurrohman; Gres Dyah Kusuma Ningrum; Hikmatul Afifah Fikriati (Jurnal Pendidikan Teknologi Informasi (JUKANTI), 2025)
This research explores the influence of implementing Augmented Reality (AR)-based instructional media on the learning motivation of ninth-grade students in Informatics class at SMP Negeri 25 Malang. A quantitative approach was applied using an ex post facto design, involving 24 students from class IX D as participants. Data collection utilized a Likert-scale questionnaire, which had undergone validity and reliability testing, resulting in a Cronbach’s Alpha score of 0.925, indicating a high level of consistency. The collected data showed a normal distribution, and linear regression analysis revealed a significance value of 0.000 (p < 0.05) and a coefficient of determination (R²) of 0.923. This implies that 92.3% of the variance in students' learning motivation can be attributed to the use of AR media. The findings demonstrate that AR significantly enhances student motivation by presenting learning content in a more engaging and interactive manner. Consequently, AR is recommended as an innovative instructional strategy to improve the learning experience in educational settings.